Medical Certification of Death and Cause of Death Statements in Cukurova University Hospital - Meral, Demet; Hilal, Ahmet; Çekin, Necmi; Gülmen, Mete Korkut; Eryılmaz, Mehmet; Akcan, Ramazan (The Bulletin of Legal Medicine, 2007)
The reliability of death statistics of countries depends on the correct information in death certificates. Death certificates are the main data source for mortality statistics in our country. We aim to evaluate the reliability of death certificates of our hospital data in this study. We evaluated the death certificate data during the period of 01.01.2004 - 12.12.2004. The retrospective analyze was performed in respect of age, gender and clinical findings. 1597 deaths were documented in this period and 920 (57.6%) cases were male. 677 (42.4%) cases were female. 179 (11.2%) cases of all were considered of medico-legal interest. In 258 (16.2%) cases the exact cause of death had not been mentioned in those certificates. Cardiopulmonary arrest, which obviously was not cause of death but somatic death labeled as a cause. We evaluated interesting findings in especially the cases that labeled as medico-legal. 17 medico-legal cases were reported as cardiopulmonary arrest, while five of them were not even documented. In six cases even the prosecutor has not been informed. Misinformation on death certificates can and may cause serious hazardous effect to final data, will be discussed widely. Key words: Death certificate, causes of death, forensic medicine.